2009
DOI: 10.2514/1.34943
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analyses of Offset-Stream Nozzles for Noise Reduction

Abstract: The Wind computational fluid dynamics code was used to perform a series of simulations on two offset stream nozzle concepts for jet noise reduction. The first concept used an S-duct to direct the secondary stream to the lower side of the nozzle. = nozzle plenum total temperature u = local axial velocity ujet = mass-averaged axial velocity of primary jet x, y, z = coordinate system ( ) = used to denote difference in discharge or thrust coefficient of the current configuration from the baseline configuration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The secondary nozzle can be tailored to induce asymmetry in the plume, at azimuthal directions where noise reduction is desired. Inducing asymmetry in the plume entails either geometrically offsetting the nozzle ducts 3,13,14 , or installing devices that deflect the bypass stream 13,15,16,17 . The misalignment between the primary and secondary streams produces a thick, lowspeed layer, that is oriented typically at downward and sideline azimuthal directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary nozzle can be tailored to induce asymmetry in the plume, at azimuthal directions where noise reduction is desired. Inducing asymmetry in the plume entails either geometrically offsetting the nozzle ducts 3,13,14 , or installing devices that deflect the bypass stream 13,15,16,17 . The misalignment between the primary and secondary streams produces a thick, lowspeed layer, that is oriented typically at downward and sideline azimuthal directions.…”
Section: Introductionmentioning
confidence: 99%
“…The enlarged secondary core reduces the convective Mach number of the primary eddies that radiate sound in the directions of the thickened coannular flow 14 . The addition of a third (tertiary) stream opens a parameter space to explore noise reduction technologies using the aforementioned methods [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetry in the nozzle entails offsetting the primary and secondary ducts, while asymmetry in the jet plume (issuing from a coaxial arrangement) can be induced by placing deflectors in the secondary stream. These "offset stream" approaches have been investigated for supersonic [13][14][15][16][17] and subsonic [16][17][18][19] jets. The acoustic benefit at supersonic speed can be substantial, while it is more moderate at subsonic speed.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Experiments and computations have revealed that the deflectors reduce the downward turbulent kinetic energy (TKE) but can also introduce a localized increase in the upward TKE. [3][4][5][6] Recent work has shown a correlation between the reduction in downward TKE and the reduction in downward peak overall sound pressure level. 7 The wedge-shaped deflector is an intriguing device with strong potential benefits but requiring great care in its design.…”
Section: Introductionmentioning
confidence: 99%